School health and nutrition environments: a multicountry survey in five countries of sub-Saharan Africa region - Burkina Faso, Ethiopia, South Africa, Sudan, and Tanzania - Noor, Ramadhani A.; Paulo, Heavenlight A.; Shinde, Sachin; Tadesse, Amare W.; Tinkasimile, Amani; Hussen, Yemisrach; Ngeba, Joyce; Sherfi, Huda; Drysdale, Roisin; Mwanyika-Sando, Mary; Codjia, Patrick; Chitekwe, Stanley; et al. (Maternal & child nutrition, 2025)
Schools are increasingly regarded as a key setting for promoting the health, well-being, and development of children and adolescents. In this multicountry cross-sectional survey, we describe the health, nutrition, and food environments of public primary schools in five urban settings in Africa region: Ouagadougou, Burkina Faso; Addis Ababa, Ethiopia; Durban; South Africa, Khartoum, Sudan; and, Dar es Salaam, Tanzania. We evaluated the school health and nutrition (SHN) environments in three main areas: (1) the availability of health-related policies, guidelines, and school curricula, (2) the provision of health, nutrition, and water, sanitation, and hygiene (WASH) services in schools, and (3) the school food environments and eating habits of adolescents. We used stratified random sampling to recruit 79 schools from five countries. Trained fieldworkers collected standardized questionnaire data from 79 school administrators, 765 food vendors, and 4999 in-school adolescents aged 10-15 years. In our study, 24 out of 79 school administrators were aware of their school's health-related policies and guidelines while 30 schools had a specific SHN curriculum. In general, health, nutrition, and WASH services were inadequate. Possibly due to a lack of school kitchens, 14.4% of students bought snacks and unhealthy foods from food vendors. Our study indicates that schools' food and nutrition environments are insufficient to improve adolescent health and nutrition in the African region, including limited coverage of SHN policies, suboptimal facilities and nutrition services, and unregulated food environments. Schools in sub-Saharan Africa need to improve their health and nutrition environments.